The European 1M+ Genomes Initiative - Moura Vicente, Astrid (2020)
Personalised Medicine - concept: Characterisation of individuals’ phenotypes and genotypes (e.g. molecular profiling, medical imaging, lifestyle data) for tailoring the right therapeutic strategy for the right person at the right time, and/or to determine the predisposition to disease and/or to deliver timely and targeted prevention". According to: Horizon2020 and the European Council Conclusions on personalised medicine for patients (2015/C 421/03)